Tingkat Literasi Digital Mahasiswa Indonesia - Yanti, Nafri; Mulyati, Yeti; Sunendar, Dadang; Damaianti, Vismaia (UNIB Press, 2021)
This study aims to obtain information about the level of digital literacy of Indonesian students. The research method used is descriptive quantitative. Based on the results of research conducted on 306 Indonesian students from several universities spread across the islands of Sumatra, Java, Sulawesi and Riau, it was found that the positive response from respondents in the aspect of information literacy was 87.27%, Digital Scholarship 93.77%, Learning Skills 85 .50%, ICT Literacy 69.50%, Privacy Management 77.57%, Communication and Collaboration 79.83% and Media Literacy 78.57%. So it can be concluded that 81.71% of respondents are used to doing daily activities that lead to indicators of a person's high level of digital literacy. The current learning process must also utilize technology according to current needs. Everyone should be able to continue to improve their digital literacy skills. This is because digital technology is also very supportive of a person's process of self-development and seeking knowledge as much as possible without any limitations of space and time.